Uji Efektivitas Handsanitizer Terhadap Daya Hambat Pertumbuhan Bakteri Staphylococcus sp dan Pseudomonas sp pada Layar Smartphone - Alverina, Yohana Thania Xena; Widyaswara, Gravinda; Sari, Ajeng Novita (Jurnal Kesehatan Rajawali, 2022)
Smartphone is a communication tool that has the potential to be contaminated with microorganisms that can be transmitted through direct contact, especially on the skin. Microbes can survive on the surface of mobile phones and serve as potential transporters of microorganisms. The use of hand sanitizer is useful for inhibiting and even killing microorganisms. Thus, the study focused on isolating bacteria from smartphone screens, especially Stappylococcus sp and Pseudomonas sp bacteria and looking at the effectiveness of hand sanitizers in inhibiting bacterial growth. This study aims to isolate Staphylococcus sp and Pseudomonas sp bacteria on smartphone screens and test the ability to use hand sanitizers against bacteria attached to smartphone screens. This type of research uses the bacterial isolation method. The target population is the academic community of the Polytechnic of St Paul Surakarta totaling 30 cell phones. The object of the research was the smartphone screen swab of the academic community for the presence of Staphylococcus sp and Pseudomonas sp bacteria and hand sanitizer as an inhibitor of bacterial growth. In 30 smartphone samples, Stapylococcus sp and Pseudomonas sp were found. This study uses the chard chart method. Hypothesis H0 did not find Staphylococcus sp and Pseudomonas sp bacteria while Ha was found Staphylococcus sp and Pseudomonas sp bacteria on the smartphone screen. In this study, the smartphone screen contained Stapylococcus sp and Pseudomonas sp bacteria, the use of hand sanitizer was effective in inhibiting bacterial growth.